Regulatory focus and perceived safety with casual partners: Implications for perceived risk and casual sex intentions during the COVID-19 pandemic - Rodrigues, D. L. (Psychology and Sexuality, 2022)
Motives for security (i.e., prevention focus) or pleasure (i.e., promotion focus) help regulate risk perceptions. Individuals focused on prevention (vs. promotion) tend to be more aware of health risks, more careful in their sexual behaviors, and less likely to take risks with casual partners. However, feeling safer with casual partners seem to mitigate some of these risks. We administered an online survey in English, Spanish, and German at the onset of the COVID-19 pandemic to 550 participants who were single (57.6% women). Participants more focused on prevention were less fearful of COVID-19 infection, perceived to be well informed about COVID-19, and retrieved their information from scientific sources. Participants more focused on promotion were more fearful of COVID-19 infection and perceived to be well informed about COVID-19 but retrieved their information from non-scientific sources. These participants also had stronger intentions to have casual sex if they felt safer (vs. less safe) with their casual partners. Our findings show the importance of individual motivations and interpersonal dynamics for risk perception and sexual activity during the pandemic.